Senam Hamil Pada Primigravida dan Lama Persalinan Exercise During Primigravida Pregnancy and Long Labor - Siti Hindun; Murdiningsih Murdiningsih; Aprillia Ayu SY (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2014)
Exercise during primigravida pregnancy is the one of method to prepare delivery process and further is to prevent maternal death. With pregnancy exercise vascularization of the uterus to the placenta becomes better that ensures the supply of oxygen and nutrients to the fetus sufficient. The objective of this research was to determine the effect of exercise during primigravida pregnancy on long labor in Widiyanti and Az Zahra Maternity Hospital. This was a observasional research. Moreover, the population involve in this research were all primigravida (mother that having first pregnancy) that done exercise pregnancy at Widiyanti and Az Zahra Maternity Hospital. The samples were taken by simple random sampling method. Furthermore, the relationship among variables was analyzed using chi square test . The result is most of women doing pregnancy exercise is 61.5%, the mother had a normal delivery time is equal to 76.9% of pregnant women with younger age (<35 years) of 100%, babies born with enough weight that 95.4%. The results of statistical tests using the chi Square found no significant association between pregnancy exercise with long labor with p values of 0.024 and OR 4.667. Conclusion, exercise pregnancy is not a major factor in determined the long labor, but health promotion by doing pregnancy exercise should be developed because it can prepare physically and psychologically of delivery process and reduce the risk of maternal death.